2023
DOI: 10.3390/su15097377
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Innovative City Pilot Policy on Industrial Structure Upgrading in China

Abstract: Urban innovation has been highly regarded as a modern urban model that drives sustainable urban development by synthesizing knowledge innovation and technological innovation in industrial processes. As such, numerous studies have emerged to investigate the impact of the innovative city pilot policy (ICP), yet the impact of the ICP on industrial structure upgrading has not been explicitly studied. To address the research gap, this study utilizes the ICP in China as a quasi-natural experiment and investigates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(85 reference statements)
0
0
0
Order By: Relevance
“…Technological innovation is essential in promoting industrial structure upgrading [43]. Innovating new technology can promote transforming and upgrading all links in the industrial chain [44]. Innovation is an essential engine for promoting industrial upgrading [45], and this main conclusion has been confirmed by most studies [46][47][48].…”
Section: The Impact Mechanismmentioning
confidence: 82%
See 1 more Smart Citation
“…Technological innovation is essential in promoting industrial structure upgrading [43]. Innovating new technology can promote transforming and upgrading all links in the industrial chain [44]. Innovation is an essential engine for promoting industrial upgrading [45], and this main conclusion has been confirmed by most studies [46][47][48].…”
Section: The Impact Mechanismmentioning
confidence: 82%
“…Moreover, technological innovation is conducive to stimulating the emergence of new industries and directly promoting the transformation of industrial structure in the direction of rationalization and advancement. At the same time, technological innovation can promote the flow of production resources from high-efficiency production sectors to low-efficiency production sectors and enhance the exchange of knowledge between industries, which in turn promotes the development of industrial structure [44,51].…”
Section: The Impact Mechanismmentioning
confidence: 99%